Combination budesonide/formoterol inhaler as maintenance and reliever therapy in Māori with asthma. Issue 6 (2nd June 2014) - Pilcher, Janine; Patel, Mitesh; Smith, Ann; Davies, Cheryl; Pritchard, Alison; Travers, Justin; Black, Peter; Weatherall, Mark; Beasley, Richard; Harwood, Matire; SMART Study Group
Abstract Background and objective There are significant health disparities between Māori and non‐Māori with asthma, a pattern seen between other ethnic populations. This study investigates outcomes for Māori in a randomized controlled trial (RCT) of combination budesonide/formoterol inhaler therapy in asthma. Methods This 24‐week multicentre RCT recruited 303 adult asthma patients, 44 of whom were Māori. Participants were randomized to the single combination budesonide/formoterol inhaler as maintenance and reliever therapy ('SMART') regimen or 'standard' regimen (combination budesonide/formoterol inhaler for maintenance and salbutamol as reliever). Outcomes included patterns of beta‐agonist inhaler use including 'high use' of reliever therapy (>8 actuations of budesonide/formoterol in excess of four maintenance doses per day for SMART and >16 actuations per day of salbutamol for standard). Differences in outcomes for Māori versus non‐Māori were assessed using an interaction term between ethnicity and treatment. Results With adjustment for ethnicity, the SMART group had fewer days of high use (relative rate (RR) 0.57 (95% confidence interval (CI): 0.38–0.85)), days of high use without medical review within 48 h (RR 0.49 (95% CI: 0.32–0.75)) and severe exacerbations (RR 0.54 (95% CI: 0.36–0.81)) compared with standard. The magnitude of the benefit from the SMART regimen was similar in Māori and non‐Māori. Regardless of treatment regimen, Māori demonstrated more days of high use, high use without medical review and underuse of maintenance therapy. Conclusions The SMART regimen has a favourable risk/benefit profile in Māori. Days of high use, days of high use without medical review and underuse of maintenance treatment were greater in Māori, regardless of treatment regimen.